PENILAIAN KINERJA, PEMERINGKATAN KINERJA DAN KEPUASAN KERJA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA SLEMAN - Uswatun Chasanah; Muhammad Heri Nugroho (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The purpose of this study is to find out about the application, advantages and disadvantages of the employee performance appraisal system and employee performance ranking and explore its relationship with employee job satisfaction at Kantor Pelayanan Pajak Pratama Sleman. To achieve these objectives, this study uses a qualitative descriptive research and data collection techniques by triangulation (a combination of observation, interviews, documentation). The results of the study indicate that the implementation of performance appraisal and performance ranking at Kantor Pelayanan Pajak Pratama Sleman is carried out based on the provisions of the Director General of Taxes Regulation number PER-12/PJ/2018. The implementation of the performance appraisal system has provided job satisfaction, so that employees are motivated to achieve the targets that have been set. Most of the informants stated that the performance rating system applied could not increase employee job satisfaction. For this reason, it is hoped that the employee performance rating system can be carried out more objectively, fairly and transparently.